Scalability Optimization of Virtualization Based Botnet Emulation Platform - Li Ruan; Bo Lin; Limin Xiao (Dianxin kexue)
Botnet emulation,a new technology to investigate Botnet characteristics,gains increasing focus.The practical virtualization based Botnet emulation platform is few and lacks support of rapid deployment,multiple virtualization,specific features of the Botnet like Botnets' circadian random shutdown and starting,and high scalability which will greatly influence the Botnet propagation emulation effect.A Botnet emulation system and its scalability improvement technologies were introduced.Experiments show that the memory performance optimization and CPU performance optimization reduce more than 77% of host memory per virtual machine,the maximum virtual machines one physical machine can starts up increase from 15 to 43; the host CPU utility is deduced from 100% to 20% when the vCPU's performance is restricted to 100 000.